Extracellular forms of A and tau from iPSC models of Alzheimer's disease disrupt synaptic plasticity - Rowan, Michael; Hu, Neng (My University, 2018)
The early stages of Alzheimer’s disease are associated with synaptic dysfunction prior to overt loss of neurons. To identify extracellular molecules that impair synaptic plasticity in the brain, we studied the secretomes of human iPSC-derived neuronal models of Alzheimer’s disease. When introduced into the rat brain, secretomes from human neurons with either a presenilin-1 mutation, amyloid precursor protein duplication, or trisomy of chromosome 21 all strongly inhibit hippocampal long-term potentiation. Synaptic dysfunction caused by presenilin-1 mutant and amyloid precusor protein duplication secretomes is mediated by Aβ peptides, whereas trisomy of chromosome 21 (trisomy 21) neuronal secretomes induce dysfunction through extracellular tau. In all cases, synaptotoxicity is relieved by antibody blockade of cellular prion protein. These data indicate that human models of Alzheimer’s disease generate distinct proteins that converge at the level of cellular prion protein to induce synaptic dysfunction in vivo.
PUBLISHED
cited By 1
Keywords: Alzheimer’s disease; Amyloid β-protein; Down syndrome; Extracellular tau; Induced pluripotent stem-cell-derived cortical neurons; Prion protein; Secretome; Trisomy 21; Dementia; Neuroscience; Age related diseases; Ageing, memory and other cognitive processes; Ageing, stroke, dementia; Neurodegeneration; Age-related disability; Mental Health/Psychosocial disability; Health